THE IMPORTANCE OF TEACHING VOCABULARY - Ismailova, Hilola (Журнал иностранных языков и лингвистики, 2021)
The article is devoted to the importance of teaching vocabulary and the five aspects of vocabulary which should be taught. Five aspects of vocabulary pronunciation, grammar, collocations, different meanings of words and sense relations between words and word formation are described in details. The article is followed by an activity which can be used in teaching vocabulary.